Integration of seasonal rainfall and irrigation into a water management plan for almond orchards: Should we irrigate in response to drought or to maintain growth potential? - Or Sperling; Niccolò Tricerri; Jessica Orozco; Zachary Ellis; Ido Gardi; Francesca Secchi; Maciej A Zwieniecki (Agricultural Water Management)
Water conservation efforts in Mediterranean climates, where summer reference evapotranspiration (ET0) far exceeds field water recharge from seasonal precipitation, have led to deficit irrigation applications. Almond (Prunus dulcis Mill) orchards can tolerate drought during the growing season without significantly impacting the current year's yield. Still, future reproductive capacity also requires water for transpiration. Almond trees must grow reproductive sites (spurs and buds) and accumulate sugars for bloom and leafing. However, the impact of droughts on canopy development and nonstructural carbohydrate storage in almond trees calls for further studies.In this study, we ask how water availability (rain and irrigation) determines orchards’ reproductive capacity. We studied ∼100 almond fields across seven almond farms in California between 2020 and 2023. We recorded seasonal irrigation amounts, climatic conditions (ET0 and rainfall), trees’ physiological status (NDVI, transpiration, nonstructural carbohydrate concentration - NSC), and seasonal yields.Water availability influenced trees’ NDVI throughout the year and determined trees’ reproductive potential. Water also affected the trees’ NSC storage in winter and their capacity for new growth in spring. Subsequently, we found a significant, although variable, nonlinear correlation between irrigation and yield (i.e., a production function) in three (out of four) study years. Yields (dry kernels) increased by ∼ 2.5 kg ha−1 mm−1 at the linear range of the regression (600–800 mm irrigation).Conclusively, delaying spring irrigation exposes trees to early-season droughts and compromises almond trees’ reproductive potential. A water budgeting approach that aims to gradually reduce available water throughout summer could substantiate a decision-support irrigation application for California almond growers. The irrigation would then proactively fit future transpiration to yield potential, rather than reactively responding to field water deficits and trees’ stress.